KORELASI FAKTOR PENGUAT (REINFORCING FAKTOR) TERHADAP KEPATUHAN MINUM OBAT ANTIRETROVIRAL (ARV) PADA PASIEN HIV/AIDS - Hidayati, Sri Aisyah; Unok, Warihan; Noorma, Nilam; Sariyani, Made Dewi (Ensiklopedia of Journal, 2024)
Abstract: Human Immunodeficiency Virus (HIV) is a virus that attacks the human immune system, which functions to fight various infections and diseases. Based on a preliminary survey conducted at RSUD Selasih, the data showed a cumulative number of PLWHA (People with HIV/AIDS) who did not attend and failed to undergo ARV treatment follow-up in the last two years. The research design used in this study was cross sectional. The study was conducted at Selasih Hospital. This study was conducted in December 2023 to all HIV/AIDS patients undergoing Antiretroviral (ARV) treatment at the VCT Clinic of Selasih Hospital. The sample amounted to 56 people. The sampling technique used Accidental Sampling. Data analysis was performed univariate and bivariate. The results showed there was a relationship between family support (p value: 0.010) and health worker support (p value: 0.035) with adherence to taking Antiretroviral drugs. It is recommended that the Hospital improve services for ODHA especially in order to increase compliance with taking antiretroviral drugs (ARV) through various information media, providing excellent service, providing motivation for ODHA and so on.Keywords: Antiretrovirals, Family Support, Health Professional Support.